A BAYESIAN APPROACH TO COMPUTING MISSING REGRESSOR VALUES (Journal of Sciences, Islamic Republic of Iran)
In this article, Lindley's measure of average information is used to measure the information contained in incomplete observations on the vector of unknown regression coefficients [9]. This measure of information may be used to compute the missing regressor values.